The Use of Evacuated Tubes for Blood Collection in Oral Anticoagulant Control - van den Besselaar, A M H P; van Halem-Visser, L P; Loeliger, E A (Thrombosis and Haemostasis, 1983)
The prothrombin time (PT) test is used to monitor oral anticoagulant therapy. Contact activation of patient blood samples in vitro may shorten the PT and thus lead to underestimation of the degree of anticoagulation. Commercial evacuated tubes for blood collection have been reported to induce shortening of the PT. The Thrombotest modification of the PT determination was used to investigate the properties of different brands of evacuated siliconized tubes. Two recently manufactured batches of such tubes did not induce appreciable shortening of the PT and can therefore be recommended for use in monitoring oral anticoagulant treatment.
Keywords: Prothrombin time; Oral anticoagulant control; Contact activation; Evacuated tubes